Brexit and Trade: Between Facts and Irrelevance - Phedon A. Nicolaides; Thibault Roy (Intereconomics, 2017)
This paper examines four claims made by Brexit supporters regarding the United Kingdom's post-exit arrangement on trade with the EU. It reviews the nature and importance of UK-EU trade links and the possible impact on the UK of leaving the EU customs union. It argues that all four of the claims are based on incongruous arguments which are either logically inconsistent or ignore the extent of the commitment required by trade agreements that tackle regulatory barriers, not just tariffs and border restrictions. We demonstrate that the attractiveness of the UK market will progressively decline as the UK enters into additional bilateral agreements. We conclude by analysing the implications for the UK of “taking back control” of its trade policy.
Keywords: 330